MENGENALKAN DAN MELESTARIKAN AKSARA JEJAWAN (SASAK) PADA MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA INDONESIA INSTITUT PENDIDIKAN NUSANTARA GLOBAL - Wahidatul Murtafi’ah; Hendri Hendri; Baiq Yulia Kurnia Wahidah (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
Jejawan (Sasak) script, also known as hanacaraka, is a traditional writing system of the Sasak tribe in Lombok, which is derived from Javanese (Kawi) script. This script is related to Javanese and Balinese scripts, which were originally written on palm leaves. The purpose of this community service is to preserve and maintain the Sasak regional culture in the form of a script that is becoming less and less known to the community itself. This research is necessary to introduce and preserve the regional culture of Sasak, Lombok, to the younger generation. This community service involved 32 students from the Indonesian Language Education Study Program in their second semester. This activity was carried out for one day, on Saturday, August 30, 2025, from 8:00 a.m. to 12:00 p.m. WITA. The initial activity involved introducing the Sasak script to the participants, followed by writing practice, and finally a reflection on the day's activities. Through this training, it is hoped that students of the Indonesian Language Education Study Program can contribute to the preservation of the Sasak script and when they enter the workforce.